Effect of nutrition education and iron-folic acid supplementation on anemia among pregnant women in Ethiopia: a quasi-experimental study - Anchamo Anato; Mensur Reshid (Scientific Reports)
Abstract The aim of this study was to assess the effect of nutrition education and counseling using health belief health model constructs along with iron-folic acid supplementation on hemoglobin level and adherence to IFAs during pregnancy. The study was a three-month quasi-experimental study design in Butajira town, Ethiopia. Community-based nutrition education and counseling sessions using the Health belief model, and IFAS for six weeks were given to the pregnant women. Compliance with iron-folic acid supplementation (IFAS) was assessed using pill counts based on the number of remaining pills in the retained prescribed bottles or strips. End-line data were collected from 97 interventions and 96 control groups of pregnant women after 6 weeks of nutrition education interventions. The analysis of the effect of the intervention was done using difference-in-difference and a generalized estimation equation (GEE) approach. At the end of the nutrition education intervention, there was a significant drop in the proportion of anemia in the intervention group compared to the control group. The prevalence of anemia among the intervention group declined from 27.8% at baseline to 7.2% after intervention. The change in the knowledge score regarding IFAS and maternal adherence to IFAS were significantly higher in the intervention group as compared to the control group (p < 0.001). In this study, the odds of adherence to IFA supplementation were 2.26 (95% CI 1.55 to 3.29) times higher among those who received nutrition education interventions as compared to the control group. Implementation of community-based nutrition education and counseling along with IFAS improved the hemoglobin level and adherence to IFAS among pregnant women. Therefore, there is need to integrate community-based nutrition education approach by using HBM constructs with antenatal IFAS distribution to improve supplementation and hemoglobin level of pregnant women.